DEVELOPINGÂ OF INQUIRY DEVICE LEARNING Â MATERIAL PLANT ORGANS FOR 11th - SUSANTI, (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Learning device in the plant organs materials on SMA GIKI 2 Surabaya not be an inquiry activities. so that, conducted research with the aim of producing learning device of inquiry feasible in materials of plant organs. This research is a development research, which adapted the 4-D model, the stage is limited to the develop stage. Subjects were the inquiry learning. Parameters of the feasibility study in terms of the results of the study include: syllabus gets a value of 89.58%, RPP gets a value of 91.67%, and LKS got a value of 94.45% and respectively categorized as very feasible. Key words: device learning; inquiry; plant organs